PENGARUH SISTEM REWARD DAN MOTIVASI BERPRESTASI TERHADAP KINERJA GURU-GURU DI SMP NEGERI SE-KECAMATAN KAMPAR TIMUR - Mardianis Mardianis; Zulfan Saam; Azhar Azhar (Universitas Riau, 2017)
The purpose of this research is to know the influence between variables (1) Systemreward with teachers performance inSMP Kampar Timur of Kampar Regency, (2) Achievementmotivation with teachers performance inSMP Kampar Timur of Kampar Regency, (3) Rewardsystem and Achievement motivation together with teachers performance inSMP Kampar Timurof Kampar Regency. This researchcarried outby spreadingthe instruments by using questionnairefor78 teachers inSMP Kampar Timur of Kampar Regency by using proportionate randomsampling technique. The instrument used to collect the data of all variables using thequestionnaire. Validity was tested using Pearson product moment formula. Instrument reliabilitycoefficient was calculated using Cronbach alpha formula. The results showed a positiverelationship between: (1) System reward toward performance of teachers with a correlationcoefficient rx1.y = 0.27 and the regression equation v = 90,126 + 0,257X1. (2) There is apositive influence between achievement motivation toward teachers performance withcorrelation coefficients rx2.y = 0.23 and the regression equation v = 98,147 + 0,180X2. (3)There is a positive influence between reward systems and achievement motivation towardteachers performance with rx1x2 y. multiple correlation coefficient = 0.28 and the regressionequation v = 89,351+ 0,221X1 + 0,042X2. The results of this study are expected to be useful forthe improvement and enhancement of teachers performance inSMP Kampar Timur of KamparRegency by increasing reward systems and achievement motivation as a teacher.